The influence of different concentrations of flavanol chocolate bars under acute supplement conditions on exercise and performance - Patel, R. K.; Brouner, J.; Allgrove, J. E.; Spendiff, O. (European Journal of Applied Physiology, 2020)
Objective: The purpose of this study was to assess the effects and acute dosage of different flavanol concentrations in a dark chocolate bar on physiological parameters during steady state (SS) and incremental exercise. Methods: In a double-blind, randomised, crossover study, 15 healthy participants with a mean ± SD age of 30 ± 7 years; stature 176.8 ± 8.6 cm and body mass 80.3 ± 8.4 kg supplemented with high flavanol (HF) (1060 mg), moderate flavanol (MF) (746 mg), low flavanol (LF) (406 mg), or a control (CON) (88 mg) chocolate bar (~ 34 g), 2 h prior to 40 min of SS cycling (80% gas-exchange threshold) followed by an incremental test to volitional fatigue. During the SS cycle oxygen consumption (VO2), respiratory exchange ratio (RER) and heart rate (HR) were continuously monitored. Plasma samples were collected prior to commencing exercise to determine nitrate (NO3-) and nitrite (NO2-) levels under each condition. Results: There was no observed effect between flavanol concentrations on VO2, RER, and HR during SS cycling (P > 0.05). VO2peak, peak power, HR peak, and RER peak also did not significantly differ between conditions (P > 0.05). There was a small trend for higher plasma NO2- levels following higher flavanol concentration; however, this did not reach statistical significance (P > 0.05). Conclusion: Acute supplementation with cocoa of differing flavanol concentrations does not appear to have any effect on exercise and performance. It is plausible that longer flavanol supplementation periods might have greater accumulative effects and thus may potentially elicit a larger effect.